Evaluation of the potential seed yield of white dover species, forms and cultivars. - Moraes, Carlos Otávio Costa; Paim, Nilton R.; Nabinger, Carlos (Pesquisa Agropecuaria Brasileira, 2014)
From March 1984 to November 1985, the potential seed yield of the native species of white dover T. riograndense Burkart and T. polymorphum Poir. was evaluated in comparison to the BR-1-Bagé, Regal, Jacuí and Guaíba cultivars of white dover (T. repens L.). The experiment was performed at the Agricultural Experiments Station of the Federal University of Rio Grande do Sul, Guaíba, RS, Brazil. The variables regarding to the seed yield and the components of the seed yield, DM yield of forage residue, percentage of crude protein (CP) and in vitro dry mater digestibility (IVOND) of the forage residue after seed harvest were evaluated. The cultivars of the white dover present differences. Rega) showed to have no adaptation for seed yield in this place. The native species T. polytnorphuni and T. riograndense (2x and 4x) showed significantly lower seed yield than the cultivars of the white dover. The autotetraploid form of T. riograndense showed no differences between variables, except for number of inflorescences/m 2 and weight of 1000 seeds, that were superior to those of the diploid form.